Digital Financial Literacy Education For Coffee Shop Businesses to Support MSME Sustainability - Nadya Annisa Nasruddin; Rahayu Alkam; Muhammad Raihan Mubaraq; Nurul Emil Safitri; Faizah Khaeruddin (PT ARRUS Intelektual Indonesia, 2026)
This community service program aimed to improve the digital financial literacy of the managers of By Bar Coffee, an MSME operating in the food and beverage (F&B) sector in Makassar City. Although the business had already adopted digital payment systems such as QRIS, the partner still faced limitations in understanding transaction security, internal controls, and digital risk mitigation. The program was expected to enhance the managers’ ability to manage digital transactions in a secure and effective manner. The program was conducted on April 15, 2026, at By Bar Coffee, Makassar, involving managers and employees responsible for financial transaction management. The methods employed included interviews to identify the partner’s needs, interactive educational sessions, demonstrations of digital transaction security practices, and mentoring through discussions and consultations. Prior to the program, participants’ understanding was largely limited to the operational use of payment applications without adequate awareness of the security risks associated with digital transactions. Following the educational sessions and mentoring activities, participants gained a better understanding of digital transaction risks, the importance of payment verification, financial data protection, and transaction security measures. Participants’ enthusiasm was reflected in their active engagement during discussions and question-and-answer sessions. The program enhanced the awareness and capability of the business managers in implementing safer and more accountable digital transaction practices. Improved digital financial literacy is expected to support operational efficiency, strengthen customer trust, and contribute to the long-term sustainability of MSMEs in the digital era.